PROPOSED EFFECTIVE WIDTH CRITERIA FOR SLAB DECK BRIDGES UNDER MILITARY TRACKED LOAD - ABDULRAHMAN, BASSAM QASIM (Journal of Duhok University, 2020)
For any slab deck bridge, the ultimate loading strength is obtained based on the distribution of that loading to a slab effective width that recommended in the adopted specifications. In this study, a simplified procedure with a design equation is presented. This procedure depends on the determination of the moments developed in a slab deck bridge and thus the slab effective width that loading is distributed to. The study employs the Iraqi military tracked load. The procedure applies to right, simply supported slab deck bridges with and without edge stiffening beams based on the aspect ratio that represents the ratio of the slab width to length. A 3D finite element analysis by a well-known programme ABAQUS was conducted to analyse the whole bridges and to give the values of moments that will be used in the derivation of an equation to calculating the slab effective width. Furthermore, a comparison between the effective width of this study and the AASHTO and LRFD specifications was conducted. It is found thatthis method gives some conservative results in comparison with AASHTO and LRFD standards because other standards have some limitations, besides not to take in consideration all the parameters required